Evaluation of a Fused FM and Cepstral-Based Speaker Recognition System on the NIST 2008 SRE - Nosratighods, M.; Thiruvaran, T.J.; Epps, J.; Ambikairajah, E.; Ma, B.; Li, H. (IEEE, 2009)
In this paper, the fusion of two speaker recognition subsystems, one based on Frequency Modulation (FM) and another on MFCC features, is reported. The motivation for their fusion was to improve the recognition accuracy across different types of channel variations, since the two features are believed to contain complementary information. It was found that the MFCC-based subsystem outperformed the FM-based subsystem on telephone conversations from NIST SRE-06 dataset, while the opposite was true for NIST SRE-08 telephone data. As a result, the FMbased subsystem performed as well as the MFCC-based subsystem and their fusion gave up to 23% relative improvement in terms of EER over the MFCC subsystem alone, when evaluated on the NIST 2008 core condition.
Keywords: Speaker Recognition; Frequency Modulation